2021
DOI: 10.1002/aepp.13175
|View full text |Cite
|
Sign up to set email alerts
|

Predicting poverty and malnutrition for targeting, mapping, monitoring, and early warning

Abstract: More frequent and severe shocks combined with more plentiful data and increasingly powerful predictive algorithms heighten the promise of data science in support of humanitarian and development programming. We advocate for embrace of, and investment in, machine learning methods for poverty and malnutrition targeting, mapping, monitoring, and early warning while also cautioning that distinct tasks require different data inputs and methods. In particular, we highlight the differences between poverty and malnutri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…We contribute to a rapidly growing literature that focuses on using new, systematized approaches to improve predictions of food security. McBride et al (2021) provide an excellent review of the existing evidence, emphasizing that these predictive models should be built for purpose.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We contribute to a rapidly growing literature that focuses on using new, systematized approaches to improve predictions of food security. McBride et al (2021) provide an excellent review of the existing evidence, emphasizing that these predictive models should be built for purpose.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Baulch and Hoddinott [5] found that 20-65% from 13 panel studies were classified as sometimes poor which were more numerous than the always poor category. McBride [31] means that being able to distinguish between structurally poor and stochastically poor is crucial for well-targeted interventions and would require models (for targeting, mapping, monitoring or early warning) to account for the structural determinants of impoverishment. This relates to the potential to observe if change occurs in either positive or negative direction.…”
Section: Measuring Povertymentioning
confidence: 99%
“…Targeting is then directed at identifying the households and individuals at risk. McBride [31] discusses the trade-offs between predictive models with hundreds of features and one that includes a few well-known easily observed variables. The latter being useful for poverty targeting, evaluation and monitoring and the former more suited for poverty mapping.…”
Section: Measuring Povertymentioning
confidence: 99%
“…Traditionally, small area estimation has been carried out by utilizing survey data to estimate a model and simulating that model in household-level census data (e.g., Elbers, Lanjouw, and Lanjouw, 2003). In the last five years, however, a growing body of innovative research has used geospatial or other big data to predict poverty and generate purely synthetic predictions of poverty or welfare, often generated by convolutional neural networks (Jean et al, 2017;Yeh et al, 2020;Engstrom et al, 2022;McBride et al 2021). These estimates are typically validated against survey data at the village level, using sample data withheld from the prediction model.…”
Section: Introductionmentioning
confidence: 99%